Effect of Face Sheet Thickness on Bending Behavior of Composite Sandwich Beam - Safaei, Babak; Karimzadeh Kolamroudi, Mohammad; Kotrasová, Kamila (American Institute of Physics Inc., 2023)
In this paper, the effect of face sheet thickness on the bending behavior of sandwich beams was investigated. The structure used for analyses was a composite sandwich beam with aluminium as skin and epoxy as core. Finite element analysis was carried out on the structure using ABAQUS software. To investigate the bending of the composite beam, three-point bending tests were performed on the material and mid-span deflections were recorded. Different results such as force vs deflection, mass, and Von Mises stress were obtained and analyzed by changing the thickness of core. Research findings revealed that the thickness of beam skin affected its mass and flexural stiffness. Moreover, as the thickness was increased, deflection was decreased if the same force was applied to the beam. As the thickness of the face was increased, beam mass was also increased. Finally, we observed that the beam with the highest thickness had the biggest Von Mises stress when the same deflection was required for different face thicknesses. © 2023 American Institute of Physics Inc.. All rights reserved.
5th International Scientific Conference on Structural and Physical Aspects of Construction Engineering 2022, SPACE 2022 -- 2022-10-12 through 2022-10-14 -- High Tatras -- 195292